Analisis Profitabilitas dalam Mengukur Kinerja Keuangan PT. Krakatau Steel, Tbk Tahun 2018-2021 - Herdina, Nova; Daryani, Ratna Kusmindian (Jurnal Bisnis dan Ekonomi, 2023)
Objective: The purpose of the research is to evaluate the financial performance of PT. Krakatau Steel, Tbk during the period 2018 to 2021 by analyzing profitability ratios.Methodology: In the framework of this research, we adopted quantitative methods and applied them with a descriptive approachResearch results: The profitability ratio of PT Krakatau Steel, Tbk from 2018 to 2021 is used as a tool to monitor the company's financial performance. The fluctuations seen in GPM indicate instability in the operational performance of these entities, reflecting problems in the company's performance. Meanwhile, there was an increase recorded in NPM, which illustrates the increase in company performance. ROA also shows an increasing trend every year.